2020
DOI: 10.1038/s41598-020-74348-7
|View full text |Cite|
|
Sign up to set email alerts
|

Sleeping late is a risk factor for myopia development amongst school-aged children in China

Abstract: Myopia, a leading cause of distance vision impairment, is projected to affect half of the world’s population in 30 years. We analysed the relationship between certain demographic, environmental, and behavioural factors and myopia from a 2-year school-based, prospective trial conducted in Shanghai, China. This trial enrolled 6295 school-aged children at baseline and followed them up for 24 months. The relationship between abovementioned factors and myopia was examined and the role of sleep in childhood myopia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
6
48
1
Order By: Relevance
“…[208][209][210][211][212][213] A large longitudinal study from Shanghai reported consistent significant associations of going to sleep late with greater myopia prevalence at baseline, incident myopia, and myopic shift in refraction, after adjustment for several variables including age, but did not find that sleep duration was an important factor. 214 The authors noted that going to sleep late was more prevalent in children who lived in urban areas, were older, had more parents with myopia, had better educated parents, tended to wake up late, spent more time reading and on screens, and spent less time outdoors -all characteristics that were also identified as risk factors for myopia. The analysis is thus highly confounded, and the evidence on causality is not strong.…”
Section: Sleepmentioning
confidence: 99%
“…[208][209][210][211][212][213] A large longitudinal study from Shanghai reported consistent significant associations of going to sleep late with greater myopia prevalence at baseline, incident myopia, and myopic shift in refraction, after adjustment for several variables including age, but did not find that sleep duration was an important factor. 214 The authors noted that going to sleep late was more prevalent in children who lived in urban areas, were older, had more parents with myopia, had better educated parents, tended to wake up late, spent more time reading and on screens, and spent less time outdoors -all characteristics that were also identified as risk factors for myopia. The analysis is thus highly confounded, and the evidence on causality is not strong.…”
Section: Sleepmentioning
confidence: 99%
“…The progression of myopia is closely related to an increased eye axis. One possible reason for the accelerated growth of the eye axis is the weakening of the structure or function of the corneoscleral[ 2 - 5 ]. Therefore, the development of myopia may be related to corneoscleral stiffness, and the mechanical properties of the biological tissue play an important role in the increase of the ocular axis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported no significant association, in adjusted models, between baseline sleep duration as continuous variable or using tertile categorization (≤ 9.56/9.57–10.00/ ≥ 10.01 h per night) and myopia progression 4 years later. The second one, by Liu et al also performed in Chinese school-aged children (6295 Chinese school-aged children (mean age 7.2 ± 0.7 years at baseline) reported no association in adjusted models between sleep duration considered in categories (< 9.5, 9.5–10, > 10 h per night) and myopia incidence and progression over 2 years, but a positive association between later bedtime (> 21h30) and myopia at baseline (6.8% of the children), 2-year myopia incidence (22%) and 2-year myopia progression 49 . However, we did not observe this association in our study.…”
Section: Discussionmentioning
confidence: 94%